Pelvic schwannoma mimicking as an adnexal mass - Poojari, Vidyashree G.; Pai, Muralidhar V.; Nambiar, Jayaraman; Mathew, Mary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Schwannoma (neurilemmomas), a peripheral nerve sheath tumour generally occurs on the head and neck region, their pelvic occurrence is much rare. Retroperitoneal schwannomas are the rarest of all retroperitoneal tumours. We report a 45 year woman with a schwannoma in the retro peritoneum that was preoperatively diagnosed as an adnexal mass.